2018
DOI: 10.3390/microorganisms6040115
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Enterohaemorrhagic Escherichia coli Survival and Virulence in the Human Gastrointestinal Tract

Abstract: Enterohaemorrhagic Escherichia coli (EHEC) is a major foodborne pathogen responsible for human diseases ranging from diarrhoea to life-threatening complications. Survival of the pathogen and modulation of virulence gene expression along the human gastrointestinal tract (GIT) are key features in bacterial pathogenesis, but remain poorly described, due to a paucity of relevant model systems. This review will provide an overview of the in vitro and in vivo studies investigating the effect of abiotic (e.g., gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 214 publications
(293 reference statements)
0
42
0
Order By: Relevance
“…62 Conflicting results were reported concerning the possible increase or, on the contrary, decrease of E. coli stx prophage induction rates by gut metabolites such as nitric oxide or bile salts (reviewed in ref. 64 ). Bile salts were also shown to induce some Salmonella prophages .…”
Section: Prophage Inductionmentioning
confidence: 99%
“…62 Conflicting results were reported concerning the possible increase or, on the contrary, decrease of E. coli stx prophage induction rates by gut metabolites such as nitric oxide or bile salts (reviewed in ref. 64 ). Bile salts were also shown to induce some Salmonella prophages .…”
Section: Prophage Inductionmentioning
confidence: 99%
“…Studies of basic microbial pathogenesis in classic pathogens such as Salmonella and enterohemorragic E. coli have revealed complex mechanisms of sensing the environment, allowing robust and rapid induction virulence gene expression under select conditions ( Duprey et al., 2014 ; Fang et al., 2016 ; Jubelin et al., 2018 ). AIEC is known to have somewhat analogous sensing machinery ( Chassaing and Darfeuille-Michaud, 2013 ; Chassaing et al., 2013 , 2011 ; Rolhion et al., 2007 ; Sevrin et al., 2020 ; Vazeille et al., 2016 ), suggesting that emulsifiers might impact bacterial surfaces due to their detergent properties.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of proteins or metabolic pathways by PICRUSt analysis revealed some microbiota features that can be linked to increased susceptibility to gut inflammation. It has been shown that several strains of E. coli use flagella to improve their mobility in the gastrointestinal tract under acidic pH and in environment with higher levels of bile salts (64). Moreover, various transmembrane secretion systems are associated with pathobionts and pathogens in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%